A novel forecasting based scheduling method for household energy management system based on deep reinforcement learning. (January 2022) - Ren, Mifeng; Liu, Xiangfei; Yang, Zhile; Zhang, Jianhua; Guo, Yuanjun; Jia, Yanbing
Highlights: A novel forecasting based reinforcement learning energy scheduling method is proposed. A GC-LSTM algorithm is adopted in out-door temperature prediction. A model-free During-DDQN algorithm is adopted to manage household energy. The proposed method performs well in the household energy management system. Abstract: The demand response (DR) strategy enables household users to actively optimize and dispatch the household energy management system (HEMS), which may significantly reduce the cost of user energy consumptions. However, the uncertainty of home users behaviors, the diversity of electrical equipment types, as well as the complexity of the working status of various devices have brought severe challenges to the home energy management system. This article proposes a new forecasting based optimization method to deliver the real-time scheduling considering the future environment trend. A recent proposed dueling based deep reinforcement learning approach is adopted to optimally dispatch the HEMS. In addition, due to the delay of heating, ventilation, and air Conditioning (HVAC) indoor and outdoor temperature data non-Gaussian, a new generalized corr-entropy assisted long short-term memory (GC-LSTM) neural network is proposed where the generalized correntropy (GC) loss function is adopted to predict the outdoor temperature. The proposed method is verified in a featured HEMS benchmark problem and the experimental results show that the user costs are effectively reduced while the user satisfaction is maintained utilizing the proposed method.